Service Safety in the Pandemic Age. (November 2020) - Berry, Leonard L.; Danaher, Tracey S.; Aksoy, Lerzan; Keiningham, Timothy L.
The service sector has been rocked by the COVID-19 pandemic. This stems in large part from the inseparable, high-contact nature of many services. During a pandemic, multiple forms of contact – customer-to-customer, customer-to-employee, employee-to-employee, and customer/employee-to-air/surfaces – can lead to serious illness or death. The urgent need for increased separability and decreased contact have led to a wave of service adaptations (firms' efforts to improve safety) and service transformations (innovations that bolster safety while offering additional benefits that are superior to what existed previously). COVID-19 has made service safety paramount, with most attention being paid to minimizing disease transmission. However, safety needs in a pandemic extend beyond physical to include interrelated domains of emotional, financial, and information safety. Physical safety is the absence of harm or injury. Emotional safety is relief from mental distress arising from pandemic-related personal traumas. Financial safety concerns minimizing economic insecurity related to the pandemic. Information safety refers to people's sense of confidence that they have the information they need to make good decisions, information that is trustworthy. We describe the unique service transformations addressing these safety concerns of Hong Kong International Airport, Henry Ford Health System (Detroit), Innocent Bystander (Australia), and Service Now that are likely to continue after the pandemic has passed. Important questions for service researchers to guide managers in reinventing how they create, deliver, and market services are highlighted.